Influence of Gaming Media Truth or Dare Regarding Pancasila Education Learning Outcomes for Class IV Students at SDN 09 Banyu Abang - Septiani, Melda; Setyowati, Dessy; Al Farisi, Salman (Lembaga Penelitian dan Pendidikan Mandala, 2024)
Formulation of the problem in this research is how the truth or dare card media influences the Pancasila education learning outcomes of Class IV students at SDN 09 Banyu Abang. This research uses experimental research with the Quasy Experiment Design method, while the research design used is Nonequivalent Control Group Design. The population in this study were all class IV students at SDN 09 Banyu Abang consisting of 14 students in class IV A and 14 students in class IV B. The samples in this study were class IV A students (Experimental Class) and class IV B students (Class Control) SDN 09 Banyu Abang. The technique used to determine the sample is a saturated sample. Data collection uses test questions. Hypothesis testing uses an independent sample t-test which begins with pre-requisite tests, namely the normality test and homogeneity test. The results of this research show that there is an influence of the truth or dare game media on the Pancasila education learning outcomes of class IV students at SDN 09 Banyu Abang. This is proven by the independent sample t-test, namely tcount (3.980) > ttable (2.056), with a significance level of 0.05. The average posttest score obtained in the experimental class was 80.21, which was better than the average posttest score obtained in the control class, namely 64.50 in the specified KKM, namely 70.